Odsunuté děti / scénáře a texty: Marek Toman, Jan Blažek ; nakreslili: Jakub Bachorík, Magdalena Rutová, Stanislav Setinský, Františka Loubat, Jindřich Janíček - Toman, Marek, 1967-; Blažek, Jan, 1977- (Post Bellum, 2021)
Pätica nemeckých pamätníkov rozpráva o svojom odsune z Československa.